HUBUNGAN SKOR SOMATOTYPE DENGAN KADAR KOLESTEROL TOTAL PADA DEWASA DINI (EARLY ADULTHOOD) YANG MEMILIKI IMT < 23 KG/M2 DI RW.2 KELURAHAN TUGU, KECAMATAN CIMANGGIS, KOTA DEPOK TAHUN 2021 - Javiera Putri Motali (2021)
Somatotype is used to describe human body shape and composition with quantitative measurement. Endomorph somatotype component has the correlation with body fatness, mesomorph with musco-skeletal robustness, and ectomorph is relative with linearity or slenderness. Endomorf measurement has the sensivity with body fatness so the blood cholesterol test was used to find the correlation.The aim of the study was to examine the association between somatotype score and blood cholesterol. The data were obtained from cross sectional study designed, the study sample were selected using purposive sampling involving 35 females and 15 males, aged 20-40 years old with BMI < 23 kg/m2. Heath-Carter anthropometric somatotype metode was employed. Bood cholesterol was measured by using finger prick digital cholesterol. The result showed that mean somatotype of females is balanced endomorph while that of males is ectomorph endomorph. From the mean somatotype in the study, indicate that females and males dominantly endomoph or has fatty body type although they have BMI < 23 kg/m2 ( normal weight or underweight nutrition status). The males respondent has linear body and the females more fatty. There is no significance correlation between three somponent somatotype and blood cholesterol.This study was found 5 people or 10% among the sample with Metabolically Obese Normal Weight (MONW) charracteristics.